Triple-wavelength depolarization-ratio profiling of Saharan dust over Barbados during SALTRACE in 2013 and 2014 - Haarig, Moritz; Ansmann, Albert; Althausen, Dietrich; Klepel, André; Groß, Silke; Freudenthaler, Volker; Toledano, Carlos; Mamouri, Rodanthi-Elisavet; Farrell, David A.; Prescod, Damien A.; Marinou, Eleni; Burton, Sharon P.; et al. (My University, 2017)
Triple-wavelength polarization lidar measurements in Saharan dust layers were performed at Barbados (13.1°N, 59.6°W), 5000-8000km west of the Saharan dust sources, in the framework of the Saharan Aerosol Long-range Transport and Aerosol-Cloud-Interaction Experiment (SALTRACE-1, June-July 2013, SALTRACE-3, June-July 2014). Three case studies are discussed. High quality was achieved by comparing the dust linear depolarization ratio profiles measured at 355, 532, and 1064nm with respective dual-wavelength (355, 532nm) depolarization ratio profiles measured with a reference lidar. A unique case of long-range transported dust over more than 12000km is presented. Saharan dust plumes crossing Barbados were measured with an airborne triple-wavelength polarization lidar over Missouri in the midwestern United States 7 days later. Similar dust optical properties and depolarization features were observed over both sites indicating almost unchanged dust properties within this 1 week of travel from the Caribbean to the United States. The main results of the triple-wavelength polarization lidar observations in the Caribbean in the summer seasons of 2013 and 2014 are summarized. On average, the particle linear depolarization ratios for aged Saharan dust were found to be 0.252±0.030 at 355nm, 0.280±0.020 at 532nm, and 0.225±0.022 at 1064nm after approximately 1 week of transport over the tropical Atlantic. Based on published simulation studies we present an attempt to explain the spectral features of the depolarization ratio of irregularly shaped mineral dust particles, and conclude that most of the irregularly shaped coarse-mode dust particles (particles with diameters & gt; 1μm) have sizes around 1.5-2μm. The SALTRACE results are also set into the context of the SAMUM-1 (Morocco, 2006) and SAMUM-2 (Cabo Verde, 2008) depolarization ratio studies. Again, only minor changes in the dust depolarization characteristics were observed on the way from the Saharan dust sources towards the Caribbean.
Keywords: Aerosol; Dust; Dust aerosols